DESIGN THINKING TOOLS FOR SCIENTIFIC STORYTELLING: A DIDACTIC INNOVATION - Rodrigues, R.; Baptista, A. E. [UNESP]; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education & Development, 2019)
What if scientists thought like designers? Would they be more creative? Design is a process of invention. If scientists thought like designers, they would probably seethe scientific path as a creation process. With this context in mind, we have designed an approach to teaching and learning the scientific storytelling structure by using the Design Thinking framework [1], and the design thinking tool visualization, and the conceptual constructs frame [2,3] and cognitive narrative [4]. We argue that scientific stories are conceptually straightforward. They explain a problem and describe a solution. The simple structure PROBLEM -> SOLUTION can be unfolded in different ways, depending on where the researcher wants to go. Imagine you are a Health Scientist from Alabama, and you have decided to conduct an experiment to learn how the children's health system of Alabama can improve health care. This is the PROBLEM you set out to solve. When you start to dig in, you realize that you need a journey mapping in order to visualize a path and test some assumptions, recognize patterns and draw conclusions. After walking through this path, you come up with a viable SOLUTION. Then you realize that your solution (X) brings a BENEFIT, and it can be applied to other situations, to help the accomplishment of Y, for instance, the development of a new computational tool to be implemented in X-like scenarios. You get so excited about your findings that you decide to begin a new path, as you realize that you have actually come up with a DIRECTION that can be applied to other fields. When we contextualize the PROBLEM -> SOLUTION structure by activating and integrating elements such as picturing a scene, picking some characters, imagining situations, adding some movement, we tell a story as we encapsulate these elements into a compact package, knowledge, information, and emotion. There is evidence that we remember things that are tied to an emotion and that stories make facts memorable [5]. Besides, stories are a fundamental way in which the brain organizes information [6], as we categorize experiences as events [7]. For both science communication and educational processes, stories are thus a valuable source of knowledge retention and knowledge transfer. When we model the scientific storytelling, we come up with a higher (cognitive) narrative. In the example, the higher narrative is PROBLEM -> SOLUTION -> BENEFIT -> DIRECTION. By modeling the scientific storytelling, we present an innovative approach for teaching and learning scientific writing, which stimulates not only the logical reasoning but also the creative process. In addition, this approach has the potential to be implemented in applications designed to assist the writing process.
Keywords: Scientific Storytelling; Design Thinking; Creative Process; Writing Process; Didactic Innovation